Effect of single Quercus ilex trees upon spatial and seasonal changes in soil water content in dehesas of central western Spain - Cubera, Elena; Moreno, Gerardo; Elena, C.; Gerardo, M. (Ann. For. Sci., 2007)
The spatial and temporal evolution of soil water content () in Quercus ilex dehesas has been investigated to determine how trees modify the soil water dynamics and the nature of tree-grass interactions in terms of soil water use in these ecosystems. Soil physical parameters and were measured at different distances from the tree trunk (2-30 m) in the upper 300 cm of soil. was measured monthly by TDR during 2002-2005. Tree water potential was determined during the summers of 2004 and 2005. At deeper soil layers, mean values were higher beyond than beneath tree canopy during dry periods. depletion beyond tree canopy continued even in summer, when herbaceous plants dried up, suggesting that trees uptake water from the whole inter-tree space. Results have shown a high dependence of trees on deep water reserves throughout late spring and summer, which helps to avoid competition for water with herbaceous vegetation.
Keywords: Oak woodland; Quercus ilex; Soil water content; TDR; tree-grass interaction